Uterus cancer: A multifactorial analysis, with emphasis on preventive methods - Almeida, Amanda Godinho Balisa; Fernandes, Ana Beatriz Paixão; Bandeira, Isabela Alves; Durães, Izadora Vieira; Ribas, Maria Clara Bandeira; Bailo, Marina Teixeira Carvalho de Abreu e Silva; Santos , Ramon Rocha Vieira; França, Dorothéa Schmidt (Seven Editora, 2023)
OBJECTIVE: To study cervical cancer in terms of its pathophysiology, risk factors, epidemiological and triggers, diagnosis, and treatment, emphasizing primary and secondary preventive methods. METHODS: A narrative literature review was performed. The electronic databases explored were Google Scholar, SCIELO (Scientific Electronic Library Online), and VHL (Virtual Health Library), in addition to the use of a virtual bibliographic collection. The coverage period included articles from 2010 to 2020. The following descriptors were applied: Uterine Cervical Neoplasms, Cytopathological Xam, Prevention, Vaccination, and HPV. RESULTS: We analyzed 16 articles covering aspects of cervical cancer, from pathophysiology, epidemiology, risk factors, and triggers, to preventive methods and management. CONCLUSION: Cervical cancer is a neoplasm caused by an infection of the HPV virus that generates great impacts on the lives of patients and that can be avoided with the use of primary and secondary preventive methods. Thus, the study presented is necessary to understand this pathology, to prevent and treat it in the best possible way. Thus, interventions aimed at minimizing the effects of this neoplasm should be carried out, such as in the Family Health Strategies (FHS) through health education projects to offer the local population complete care. DOI:https://doi.org/10.56238/devopinterscie-261